The Patterns of China's Outward Foreign Direct Investment - Liu, Wengang (2006)
Over the past two decades, China's inward foreign direct investment (FDI) has attracted worldwide scholars' research interests. In contrast, the emerging outward FDI trend has received much less attention. Existing mainstream international business theories were mainly derived from the experience of western multinationals. Whether and to what extent they can apply to the case of Chinese outward FDI is questionable. To this end, this research is conducted to explore the patterns and distinct characteristics of China's outward FDI, specifically on entry modes, destinations and the role of the Chinese government.